No Pass No Drive: Education and Allocation of Time - BARUA, Rashmi Rekha (Institutional Knowledge at Singapore Management University, 2013)
Since the late 1980s, several states in the US have introduced No Pass No Drive (NPND) laws that set minimum academic requirements for teenagers under 18 to obtain a driving license. Using data from the U.S. Census and Monitoring the Future (MTF) survey, we exploit cross-state, cross-cohort and cross-time variation in NPND laws to study their effect on educational outcomes and allocation of time among teenagers. Estimates using the Census show that NPND laws have a positive and significant effect on both years of completed schooling and the probability of high school completion among boys and blacks, but not girls. Our results are robust with respect to several internal validity checks. Using the MTF, we show that NPND laws were effective in reducing truancy. We also find evidence of increased time allocated to school-work at the expense of leisure and employment activities.